2019
DOI: 10.1364/oe.27.003761
|View full text |Cite
|
Sign up to set email alerts
|

Circularly polarized extreme ultraviolet high harmonic generation in graphene

Abstract: Circularly polarized extreme ultraviolet (XUV) radiation is highly interesting for investigation of chirality-sensitive light-matter interactions. Recent breakthroughs have enabled generation of such light sources via high harmonic generation (HHG) from rare gases. There is a growing interest in extending HHG medium from gases to solids, especially to 2D materials, as they hold great promise to develop ultra-compact solid-state photonic devices and provide insights into electronic properties of the materials t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 55 publications
4
27
0
1
Order By: Relevance
“…Thus the G/hBN heterostructure as a new layered material combines and extends the HHG properties of the constituent layers. Apart from these, by orienting the linearly polarized laser field along the zigzag and armchair directions, we have observed anisotropic harmonic emission in G/hBN, similar to that being reported in graphene 28 and hBN. 36…”
Section: High Harmonic Spectrasupporting
confidence: 85%
See 1 more Smart Citation
“…Thus the G/hBN heterostructure as a new layered material combines and extends the HHG properties of the constituent layers. Apart from these, by orienting the linearly polarized laser field along the zigzag and armchair directions, we have observed anisotropic harmonic emission in G/hBN, similar to that being reported in graphene 28 and hBN. 36…”
Section: High Harmonic Spectrasupporting
confidence: 85%
“…High harmonic generation (HHG) in 2D materials has attracted much attention, alongside the emergence of the new research frontier of HHG in solids, 4,5 which is of great importance for the exploration of strong-field physics in condensed matter systems [6][7][8][9][10][11] and for the development of novel ultrafast optoelectronic and photonic applications. [12][13][14][15][16] HHG in graphene, [17][18][19][20][21][22][23][24][25][26][27][28] silicene, 29 black phosphorous, 30 transition metal dichalcogenides, [31][32][33][34] and hexagonal boron nitride (hBN) [35][36][37] has been investigated theoretically and/or experimentally. Yet, these studies only focus on 2D materials in the form of monolayers or multilayers composed of the same material.…”
Section: Introductionmentioning
confidence: 99%
“…Current research of HHG in 2D materials has been primarily focused on graphene, [64][65][66][67][72][73][74][75][76][77][78][79][80][81][82][83] the most known prototype atomically thin material. Besides, studies of HHG in silicene, 84 hBN, 68,70 and MoS 2 63,85 have also been reported.…”
Section: Superior Hhg Propertiesmentioning
confidence: 99%
“…Моделирование процессов отклика графена на действие внешнего электрического поля позволяет оценивать характеристики перспективных решений на базе этого материала для большого диапазона частот, интенсивностей и длительностей импульса [1][2][3][4]. Включение внешнего поля запускает процесс рождения свободных носителей и их последующей эволюции.…”
Section: Introductionunclassified